Pursuing Sustainability: A Guide to the Science and Practice - Matson, Pamela; Clark , William C.; Andersson, Krister Par (Princeton, New Jersey: Princeton University Press, 2016)
"Sustainability is a global imperative and a scientific challenge like no other. This concise guide provides students and practitioners with a strategic framework for linking knowledge with action in the pursuit of sustainable development, and serves as an invaluable companion to more narrowly focused courses dealing with sustainability in particular sectors such as energy, food, water, and housing, or in particular regions of the world. Written by leading experts, Pursuing Sustainability shows how more inclusive and interdisciplinary approaches and systems perspectives can help you achieve your sustainability objectives. It stresses the need for understanding how capital assets are linked to sustainability goals through the complex adaptive dynamics of social-environmental systems, how committed people can use governance processes to alter those dynamics, and how successful interventions can be shaped through collaborations among researchers and practitioners on the ground. The ideal textbook for undergraduate and graduate students and an invaluable resource for anyone working in this fast-growing field, Pursuing Sustainability also features case studies, a glossary, and suggestions for further reading. Provides a strategic framework for linking knowledge with action Draws on the latest cutting-edge science and practices. Serves as the ideal companion text to more narrowly focused courses. Utilizes interdisciplinary approaches and systems perspectives. Illustrates concepts with a core set of case studies used throughout the book. Written by world authorities on sustainability. An online illustration package is available to professors"
Keywords: Sustainability| Sustainable development| Environmental responsibility| POLITICAL SCIENCE / Public Policy / Environmental Policy; NATURE / Ecology | NATURE / Environmental Conservation & Protection